Problem-solving in multi-level governance decision-making contexts: Case Bergen Light Rail - Stenhäll, Jaakko; Rossi, Paula (Palgrave Macmillan, 2026)
This chapter focuses on problem-solving in multi-level governance decision-making context by presenting a Norwegian case of a transit-oriented urban development project, the Bergen light rail. In various European cities, modern light rail system projects have been influential for urban development. The aims of such projects are often aimed at addressing, for example, development for city economics as well as environmental challenges, and creating solutions and well-being for citizens through better mobility and preventing segregation. To achieve these solutions, innovative problem-solving is called after. The Bergen case study offers a possibility for an in-depth analysis of problem-solving in local governance. We focus on a context-dependent transit-oriented development project through an integrated theoretical approach drawing insights from multi-level governance and problem-solving literature. Empirical data and data analysis focus on the Bergen light rail case through project documentation and interviews with key actors. As a conclusion, we provide an increased understanding of problem-solving in multi-level governance settings by exploring of what guides the decision-making in complex multi-level settings, and what kind of implications the decision-making context has on the problem-solving processes in urban development projects.
Keywords: Multi-level governance; Light rail; Innovative problem-solving; Decision-making; Urban development projects; fi=Julkisjohtaminen|en=Public Management|